TEACHING PRESENCE AND ITS IMPACT ON STUDENT ENGAGEMENT AND SENSE OF COMMUNITY IN BLENDED BUSINESS ENGLISH - Suharno, Suharno; Musthafa, Bachrudin; Purnawarman, Pupung (University of Kuningan, 2025)
This study emphasized the critical role of teaching presence in enhancing student engagement and fostering a sense of community in blended business English learning environments. As blended learning becomes increasingly popular, understanding how instructors' active participation, feedback, and facilitation impact student outcomes is essential. The research utilized a mixed-method approach, combining quantitative surveys with qualitative interviews among university-level business English students and their instructors. Key findings revealed that a strong teaching presence boosted student participation, while constructive feedback motivated improved performance. Additionally, effective facilitation by instructors helped create supportive communities, encouraging collaboration and teamwork among students. These insights underscore the importance of active instructor involvement in blended learning to maximize educational outcomes. Educators are advised to maintain high levels of teaching presence and leverage feedback to stimulate dynamic student interactions, thereby fostering an engaging and cohesive learning environment. This study contributes practical recommendations for optimizing business English instruction in mixed-mode settings. The sample size was the obvious limitation to address to yield a more reliable study result.